Caracterização cardíaca em serpentes da espécie Pantherophis Guttatus usando variabilidade da frequência cardíaca - (:unkn) unknown (Universidade Brasil, 2021)
The use of electrocardiogram in reptiles can be an tool to monitor cardiac function in reptiles, however this technique is not broadly used, due to a limited understanding of its interpretation. This study analyzed the Heart Rate Variability (HRV) in Pantherophis guttatus snakes; animals that are endemic to the United States but distributed globally as a pet. Several cardiac diseases have been described for reptiles, however, for the studied snakes, these diseases are rarely diagnostic and in most cases the information is only based on the postmortem analysis. The use of linear HRV methods can contribute to the understanding of cardiac physiology, providing information for the diagnosis and prognosis of heart disease in snakes. Twenty-one snakes were used for the study (female=8, male=13) the snakes were not sedated. HRV parameters were made based on electrocardiographic records (ECG) and the RR intervals record were analyzed by non-linear methods, in the time and frequency domains. Significant differences were observed in the RR intervals for female and male snakes, varying by 18.8% and 15.3%, frequency. For the frequency of domain, the values varied between high and low. The changes observed in the time domain can be explained for the control of the autonomic nervous system by the action of the parasympathetic system, which is confirmed by the variations in the frequency domain. Even though significant differences were observed for cardiological variables between males and females, there is no way to infer the existence of pathological processes in any of the groups of snakes. To the best of our knowledge, this is the first time that the values established for SD1 and SD2, as well as the values of the frequency domain, with emphasis on the LF widely used in study in other species, were used to evaluate the cardiac function in Pantherophis.guttatus snakes.
Keywords: Serpentes; Eletrocardiograma; Variabilidade Frequência Cardíaca; Engenharia Biomédica (Bioengenharia)